The Loner : The Blood of Renegades - Book 10 - Johnstone, J. A. (New York : Pinnacle Books, 2011)
The damsel is in distress, or so it seems to Conrad Browning. On his way across the wide, tall Utah territory to California, the Loner meets a beautiful Mormon girl on the run from a forced wedding-and the gun-toting faithful trying to hunt her down. But there are two sides to every story-and the ones you dont hear are the ones that can get you killed. The runaway bride has a little history of her own. Soon, the Loner touches off a storm of unholy gunfire, drawing blood from an outlaw and a death sentence from a patriarch. Among murderers and Mormons, Bibles and bullets, the Loner finds himself riding to a wedding-a ceremony he intends to crash with a vengeance.
Keywords: Morgan, Conrad -- (Fictitious character) -- Fiction; Forced marriage; Fiction; Escapes -- Fiction; Latter Day Saint women -- Fiction; Rescues -- Fiction; Western fiction